Positive and negative aspects of remote learning during the COVID-19 pandemic in the view of Brazilian university students who received university assistance - Capellini, Vera Lucia Messias Fialho [UNESP]; Zhang, Jie; Garcia, Luciana Marolla [UNESP]; Hashimoto, Marcelo Setsuo [UNESP]; da Rocha, Eduardo Pimentel [UNESP] (Frontiers, 2025)
Introduction: The COVID-19 pandemic generated concerns about people’s life and future globally. Regarding education, students worldwide faced problems (personal, social and/or economic) to continue studying. In this study, we investigated the perceptions of Brazilian undergraduate students who received university assistance during the COVID-19 pandemic, examining the positive and negative aspects of remote learning and assessing the impact of the assistance on student retention at the university. Methods: 127 students participated in the study. Data was obtained through an online survey. The snowball technique was used to collect data. Results: Being close to family, reduced expenses on campus, flexible schedules, and the ability to review lessons and related materials outside of class were the positive factors listed by the students. These positive factors may have contributed to reducing stress caused by COVID-19, increasing student retention and course completion rate, and improving student’s quality of life. On the contrary, participants reported negative aspects, such as lack of internet access, excess of activities, concerns about teaching quality, inadequate study environments, family-related problems, and insufficient materials and technology tools. Discussion: Despite the fears and insecurities, the pandemic brought to the students, our study found that the help offered by the university to students proved to be beneficial, positively impacting student development and retention. Notably, 89 participating students (70.08%) completed all courses without experiencing any personal, social, or educational setbacks caused by the pandemic.
Keywords: COVID-19; pandemic; remote learning; university assistance; university students